2014
DOI: 10.4049/jimmunol.1400523
|View full text |Cite
|
Sign up to set email alerts
|

Bispecificity for Myelin and Neuronal Self-Antigens Is a Common Feature of CD4 T Cells in C57BL/6 Mice

Abstract: The recognition of multiple ligands by a single TCR is an intrinsic feature of T cell biology, with important consequences for physiological and pathological processes. Polyspecific T cells targeting distinct self-antigens have been identified in healthy individuals as well as in the context of autoimmunity. We have previously shown that the 2D2 TCR recognizes the myelin oligodendrocyte glycoprotein epitope (MOG)35–55 as well as an epitope within the axonal protein neurofilament medium (NF-M15–35) in H-2b mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 73 publications
(257 reference statements)
1
21
0
Order By: Relevance
“…that NFM expression was not required for T cell mediated EAE (59). This is consistent with the reports that proliferation and cytokine production by MOG specific T cells were markedly diminished by restimulation with NFM compared to cognate MOG (28, 40, 59). We support that CNS T cell infiltrates are functionally responsive to NFM during EAE (14, 28), because pMHC monomers detected T cell cross-recognition of MOG 38-49 and NFM 18-30 by the majority of infiltrates at peak and chronic time points (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…that NFM expression was not required for T cell mediated EAE (59). This is consistent with the reports that proliferation and cytokine production by MOG specific T cells were markedly diminished by restimulation with NFM compared to cognate MOG (28, 40, 59). We support that CNS T cell infiltrates are functionally responsive to NFM during EAE (14, 28), because pMHC monomers detected T cell cross-recognition of MOG 38-49 and NFM 18-30 by the majority of infiltrates at peak and chronic time points (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Our group also found this true for a model antigen system (58). It is not totally unexpected that deletion failed to alter the NFM specific T cell response considering the MHC alterations inherent in NFM 15-35 elicit a weaker association for I-A b than MOG 35-55 (28), which is consistent with the high concentration of NFM required to tolerize EAE compared to MOG (59). In support of this, our studies revealed that cross-reactivity was not altered between wild type and NFM -/- mice because MOG 35-55 induced EAE similarly in both mouse strains (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations